Yoga Increases the Quality of Sleep in Menopause Women - Fara, Yetty Dwi; Pujiastuti, Rr. Sri Endang; Hadisaputro, Suharyo (Indonesian Journal of Medicine, 2019)
Background: Menopausal women experience various changes, physical, psychological, and hormonal changes that cause menopausal symptoms. During menopause, women experience sleep disorders and some experience insomnia. Lifestyle changes are one way to reduce menopausal symptoms, such as physical activity. Physical activities such as yoga can stimulate a relaxation response both physically and psychologically that can reduce physical and psychological symptoms in menopausal women. The aim of this study was to examine the effect of yoga interventions on the sleep quality of menopausal women.Subjects and Method: This was a quasi-experiment with a non-equivalent control group design. The study was conducted in the Gedawang-Banyumanik area, Semarang, Central Java. A total of 22 study subjects was collected by purposive sampling. The dependent variable was the quality of sleep. The independent variable was yoga. The quality of sleep was measured using the Pittsburgh Sleep Quality Index (PSQI).Results: Poor quality of sleep score decreased by 10.73 after yoga intervention (95% CI= -4.30 to -0.26; p= 0.029).Conclusion: Yoga interventions improve the quality of sleep in menopausal women.Keywords: quality of sleep, yoga, menopausal womenCorrespondence: Yetty Dwi Fara. Midwifery Program, School of Health Polytechnics Semarang. Jl. Tirto Agung Pedalangan, Banyumanik, Semarang, Central Java, 50239. Email: yettydwifara@gmail.com. Mobile: 085279545189.Indonesian Journal of Medicine (2019), 4(3): 278-284https://doi.org/10.26911/theijmed.2019.04.03.11